2016
DOI: 10.5114/aoms.2015.54791
|View full text |Cite
|
Sign up to set email alerts
|

Activated factor IX, factor XI and tissue factor identify patients with permanent atrial fibrillation treated with warfarin who are at risk of ischemic stroke

Abstract: IntroductionPreviously, we have demonstrated that significant proportions of patients with various cardiovascular diseases have active tissue factor and active factor XIa in their plasma. In the current study, we evaluated active tissue factor and active factors (F)XI and FIX in plasma from patients with atrial fibrillation.Material and methodsIn 110 consecutive patients with permanent atrial fibrillation receiving warfarin, we determined active tissue factor, together with plasma FIXa and FXIa, using clotting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
(35 reference statements)
0
19
0
Order By: Relevance
“…The absence of a clearly defined relationship or correspondence of FIXa to either injury severity and/or shock is consistent with a previous study that suggested the mechanism of regulating FIXa generation and longevity differs from those observed for TF and FXIa. 50 …”
Section: Discussionmentioning
confidence: 99%
“…The absence of a clearly defined relationship or correspondence of FIXa to either injury severity and/or shock is consistent with a previous study that suggested the mechanism of regulating FIXa generation and longevity differs from those observed for TF and FXIa. 50 …”
Section: Discussionmentioning
confidence: 99%
“…Twenty-five studies were excluded by reading the text of the article: 6 studies were not related to AF or prognosis of AF, 4 studies lacked any of our requisite data, 3 studies were not used for assessment of vWF and 12 were not prospective cohort studies. Finally, 12 studies were included 21 25 28–35 39–41. A flow diagram of our search for articles is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies21 28–31 33 40 41 reported correlations between vWF levels and stroke. Meta-analysis showed that six studies21 28–31 33 with a follow-up of ≥3 years found that high vWF levels did not increase the risk of stroke in patients with AF (RR 1.64; 95% CI 0.98 to 2.76), but two studies40 41 with a follow-up of <3 years found that high vWF levels increased the risk of stroke in AF patients (RR 1.8; 95% CI 1.09 to 2.98) (figure 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particular attention should be paid to the group of patients with cardiovascular disease, e.g. permanent atrial fibrillation, who present chronic changes in haemostasis and higher thromboembolic risk [24].…”
Section: Von Willebrand Factormentioning
confidence: 99%